Resiliensi Spiritual Perempuan Kristen: Kajian Teologi Feminis atas Narasi Perempuan dalam Studi Perjanjian Baru - Aya Susanti; Sarah Wassar (Sabda: Jurnal Teologi Kristen, 2024)
Spiritual resilience is an important aspect of the lives of Christian women as it relates to their ability to socialise and develop their spiritual lives. In societies still influenced by patriarchal constructs, women often face marginalisation and, inevitably, limitations in gaining recognition for their spiritual roles and experiences. The theological foundations for the development of women’s spirituality have not yet been fully explored. This study aims to analyse the spiritual resilience of Christian women through a feminist theological examination of women’s narratives in the New Testament. It employs a qualitative method using a literature review approach. It can therefore be concluded that the spiritual resilience of Christian women in New Testament narratives is formed through a deep relationship with God in the face of marginalisation, as well as the courage to fulfil their spiritual calling amidst patriarchal social structures. The reinterpretation of women’s narratives through a feminist theological perspective affirms that women are active subjects in God’s work of salvation, making a significant contribution to the formation of spirituality. These findings result in the construction of a model of Christian women’s spiritual resilience that is relevant to the development of feminist theology and provides practical implications for church ministry.  AbstrakResiliensi spiritual merupakan aspek penting dalam kehidupan perempuan Kristen karena berkaitan dengan kemampuan bersosial dan membangun kehidupan rohani.  Masyarakat yang masih dipengaruhi oleh konstruksi patriarkal, perempuan sering menghadapi marginalisasi, dan tentunya keterbatasan dalam memperoleh pengakuan terhadap peran dan pengalaman spiritualnya. Peologisnya bagi pengembangan spiritualitas perempuan belum dieksplorasi secara optimal. Penelitian ini bertujuan menganalisis resiliensi spiritual perempuan Kristen melalui kajian teologi feminis atas narasi perempuan dalam Perjanjian Baru. Menggunakan metode kualitatif dengan pendekatan studi pustaka. Maka dapat disimpulkan bahwa resiliensi spiritual perempuan Kristen dalam narasi Perjanjian Baru terbentuk melalui relasi yang mendalam dengan Allah dalam menghadapi marginalisasi, serta keberanian menjalankan panggilan spiritual di tengah struktur sosial yang patriarkal. Reinterpretasi narasi perempuan melalui perspektif teologi feminis menegaskan bahwa perempuan merupakan subjek aktif dalam karya keselamatan Allah yang memiliki kontribusi signifikan bagi pembentukan spiritualitas. Temuan ini menghasilkan konstruksi model resiliensi spiritual perempuan Kristen yang relevan bagi pengembangan teologi feminis serta memberikan implikasi praktis bagi pelayanan gereja. Kata Kunci: Resiliensi Spiritual; Perempuan Kristen; Teologi Feminis; Narasi Perempuan